Cheap-talk Communication in Procurement Auctions: Theory and Experiment - Sander Onderstal; Yang Yang (Tinbergen Institute, 2020)
In procurement auctions, bidders are usually better informed about technical, financial, or legal aspects of the goods and services procured. Therefore, the buyer may include a dialogue in the procurement procedure which enables the suppliers to reveal information that will help the buyer to better specify the terms of the contract. This paper addresses the question of the value added of letting the sourcing process consist of both an auction and a negotiation stage, theoretically and in a laboratory experiment. Our theoretical results suggest that in a setting where the buyer and the suppliers have aligned interests regarding the terms of the contract, allowing the winning supplier to communicate with the buyer after the auction is beneficial to the buyer compared to no communication and ex-ante communication. In a setting where the buyer and the winning supplier have misaligned interests regarding the terms, the buyer benefits from ex-ante communication relative to no communication and ex-post communication. Our experimental data provide strong evidence for the predictions in the aligned-interest setting. In the misaligned-interest setting, we do not observe significant differences between the three mechanisms. Our experimental findings offer several managerial implications for the appropriate design of sourcing processes.
Keywords: C92; D44; D82; 330; Procurement auctions; bidding; cheap-talk communication; negotiations; game theory; experimental economics